Pharmacokinetics of ceftazidime administered to lactating and non-lactating goats - Villagra, Sergio (2011)
The aim of this work was to determine the pharmacokinetics of intravenous (iv) and intramuscular (im) ceftazidime administered to lactating (LTG; n = 6) and non-lactating (NLTG; n=6) healthy Creole goats in 2 trials (T1 and T2). During T1 and T2, goats randomly received a single dose of im or iv ceftazidime (10 mg/kg). Serum concentration of iv ceftazidime in NLTG and LTG goats is best described by 2 and 3 compartment models, respectively. The pharmacokinetic parameters of iv and im ceftazidime administered to LTGandNLTGshowed statistically significant differences (P<0.05) in the constants (äz, T1 vs T2 [iv] 0.5±0.1 vs 0.3±0.1 /h; T1 vs T2 [im] 0.5±0.2 vs 0.3±0.1 /h) and in the mean times (t1/2, T 1 vs T 2 [iv] 1.6±0.3 vs 2.3±0.6 h; T 1 vs T 2 [im] 1.6±0.7 vs 2.6±0.9 h) of elimination. The bioavailability of ceftazidime in LTG and NLTG was 113.0 ± 17.8 and 96.0 ± 18.0 %, respectively. Ceftazidime concentration in milk at 2 h was: iv = 1.9 ± 0.2 and im = 2.4 ± 0.5 μg/m; the penetration in milk was iv = 18.3 ± 13.5 and im = 14.3 ± 10.6 %. Ninety-six hours after iv and im administration, residues of the drug were not found in milk. In conclusion, ceftazidime, when administered to goats, showed high concentration times in serum, good penetration into milk and a bioavailability that makes it suitable to be used by the im route.